Schoolbag-Weights and Musculo-Skeletal Complaints in Three Schools In Rural Maharashtra - Shyam V Ashtekar; Jagdish D Powar; Siddiqui Aqsa; Shekhar B Padhyegurjar; Manasi S Padhyegurjar; Ashish Banginwar (Medsci Publications, 2017)
Introduction: Heavy school-bags and the musculo-skeletal complaints are common concerns across countries, but Indian rural studies are scant. This rural study was undertaken to explore school-bag weights, and association of bag-weights with reported pain/discomfort. Methods: This is a cross sectional study covering 261 students (m 128, f 131) in 8th and 9th divisions in 3 rural schools in Nashik district. Standard procedures were used for anthropometry and school-bag weights. Reported musculo-skeletal complaints were ascertained with structured questionnaire. Teachers were interviewed. Excel and Epi-Info were used for analysis. Results: Average schoolbag-weight was 3.7kg.47% schoolbags weighed>10% bodyweight. More girls than boys had heavy bag-packs and musculoskeletal complaints. Heavy school-bags and musculoskeletal complaints showed association with Chi-square; but a t-test showed no association of musculoskeletal complaints with product of bag-weight and walking-duration; while domestic /farm work were confounding variables. Teachers were aware of bag-weight guidelines and health issues but not about the problem in their schools. Conclusions: Despite awareness, these rural schools had sizeable proportion of heavy bags. Hence counseling of stakeholders and reworking classroom schedules are necessary for safety limits.